Analysis of Connexin37 gene C1019T polymorphism and PCOS susceptibility in South Indian population: case–control study. (January 2016) - Guruvaiah, Praveen; Govatati, Suresh; Reddy, Tumu Venkat; Beeram, Himabindu; Deenadayal, Mamata; Shivaji, Sisinthy; Bhanoori, Manjula
Abstract: Objective: Polycystic ovarian syndrome (PCOS) is a complex and multifactorial disorder believed to be the consequence of a complex interaction between genetic, immunological, and environmental factors. The main aim of this study was to investigate the association of Connexin37 ( Cx37 )/Gap junction alpha 4 (GJA4) gene C1019T single nucleotide polymorphism (SNP) with the susceptibility to polycystic ovarian syndrome (PCOS) in South Indian women. Study design: This study comprises 98 PCOS patients and 100 healthy women without PCOS of South Indian origin. We genotyped total of seventeen selected Cx37 SNPs including C1019T (rs1764391) by polymerase chain reaction and sequencing analysis. The genotype frequency and allele distributions of cases and controls were analyzed using Fisher's exact test. Results: The genotype and allele frequencies of the C1019T polymorphism significantly differ between cases and controls. The frequencies of C/C genotype ( P = 0.009) and ' C ' allele ( P = 0.002) of the C1019T polymorphism showed a significant prevalence in cases compared to controls. Conclusion: Our findings suggest that the Cx37 C1019T variation may contribute to the risk of PCOS in the South Indian women.